Konsep Pendidikan Agama islam Berwawasan Multikultural - Dian Safitri; M Anas Taufiqurrohman; Ahmad Manshur (STKIP Subang, 2026)
The development of Islamic religious education based on multicultural insights in schools has become an urgent need in the context of an increasingly pluralistic society. This study aims to analyze the concepts, implementation, and challenges in applying multicultural Islamic religious education in schools. The methods used include literature review and descriptive analysis of multicultural education practices in various educational institutions. The findings indicate that a multicultural approach in Islamic religious education can help students understand the values of diversity, respect differences, and strengthen interfaith tolerance. Development strategies include integrating multicultural values into the curriculum, providing teacher training to enhance multicultural competencies, and creating an inclusive learning environment. The challenges faced include a lack of teacher understanding of multicultural education, resistance to change, and limited policy support. Therefore, synergy between the government, schools, teachers, and society is necessary to realize Islamic religious education that aligns with the spirit of pluralism and social justice.